Pemanfaatan Youtube sebagai Sumber Pembelajaran untuk Mahasiswa - Damayanti, Ning T.; Juliawati, Mita (e-GiGi, 2025)
Abstract: Technological changes have significant impacts on the field of education. Education via YouTube has increased and has a high rating in the educational sector. Modification of the learning system through social media will become a source of student learning, including clinical tutorials. This study aimed to find out an overview of the utilization of YouTube as a learning resource for students at the Faculty of Dentistry. This was a descriptive and observational study with a cross-sectional design. Respondents were students at the Faculty of Dentistry, Universitas Trisakti class of 2020-2022. Data were obtained from 261 respondents using an online questionnaire through Google form media. Data analysis were presented descriptively with frequency distribution data in the form of tables and diagrams using SPSS. The results showed that the majority of respondents (84.29%) agreed with the statement that YouTube could be an accessible source of learning material with the largest number being the class of 2021 (39.1%), followed by class of 2020 (31.8%) and class of 2022 (29.1%). In conclusion, the utilization of YouTube is important as a source of student learning, one of which is in the clinical tutorial learning process. Keywords: YouTube; clinical tutorials; learning source; students    Abstrak: Perubahan teknologi memiliki dampak yang signifikan dalam bidang pendidikan. Edukasi melalui YouTube pada bidang pendidikan mengalami peningkatan dan menduduki rating yang tinggi. Modifikasi sistem pembelajaran melalui media sosial akan menjadi sumber pembelajaran mahasiswa antara lain tutorial klinik. Penelitian ini bertujuan untuk mengetahui gambaran penggunaan YouTube sebagai sumber pembelajaran mahasiswa Fakultas Kedokteran Gigi. Jenis penelitian ialah observasional deskriptif dengan desain potong lintang. Responden ialah mahasiswa/mahasiswi Fakultas Kedokteran Gigi Universitas Trisakti Angkatan 2020-2022. Pengambilan data diperoleh dari 261 responden menggunakan kuesioner secara online dengan media Google form. Analisis data disajikan secara deskriptif dengan data distribusi frekuensi dalam bentuk tabel dan diagram menggunakan SPSS. Hasil penelitian mendapatkan mayoritas responden (84,29%) menyatakan setuju pada pernyataan YouTube dapat menjadi akses untuk sumber materi pembelajaran dengan angkatan paling banyak ialah pada angkatan tahun 2021 (39,1%), diikuti angkatan 2020 (31,8%), dan angkatan 2022 (29,1%). Simpulan penelitian ini ialah penggunaan YouTube penting sebagai sumber pembelajaran mahasiswa salah satunya dalam proses pembelajaran tutorial klinik. Kata kunci: YouTube; tutorial klinik; media pembelajaran; mahasiswa